Interação fluido-estrutura em cilindros utilizando dinâmica dos fluidos computacional - Ribera, Rodrigo Lisita (2007)
The purpose of this work was the development of a computer code for structural systems to be coupled with the code for tridimensional flow calculus, with the physical virtual model, developed at the Laboratory of Heat and Mass Transfer and Fluid Dynamics (LTCM), (named Fluids3D), allowing the numerical simulation and analysis of the fluid structure interaction over tridimensional deformable geometries. For the structure solution four versions of the code were developed; the first one uses the finite difference method for the discretizations of the spatial term of the Euller Bernoulli beam equation and fourth order Runge-Kutta method for the temporal solution term and the three others use the finite element method for the structural discretization and the direct integration method of Newmark Beta for the resolution of the transient term. In the second and third versions, respectively, were used beam elements with three and six degrees of freedom per node. In the fourth, the global matrices were assembled based on the elemental matrices obtained from commercial code. The initial interest was in the analysis of flow over risers and the entire dissertation was developed with this focus. However, fluid-structure interaction is a field with lots of applications, and with the perspective that this line of research will increase at the LTCM, a structural code allowing the simulation of geometries others than the cylindric was developed. The preliminary results are very promising, as the coupled simulations are converging and presenting consistent results. With the computational capacity of the LTCM gradually increasing, we hope that the simulation of risers with large aspect ratios will be, soon, possibly to be executed.